Temporal and stoichiometric patterns of algal stimulation of litter‐associated heterotrophic microbial activity. (11th December 2019) - Francoeur, Steven N.; Neely, Robert K.; Underwood, Savannah; Kuehn, Kevin A.
Abstract: Periphyton communities associated with submerged plant detritus contain interacting autotrophic and heterotrophic microbes, and are sites of extracellular enzymatic activity. The strength and nature of these interactions might be expected to change over time as microbial communities develop on plant litter. Microbial interactions and enzymatic activity can be altered by nutrient availability, suggesting that litter stoichiometry could also affect these phenomena. We grew wetland plants under ambient and nutrient‐enriched conditions to generate plant litter of differing nutrient content. In two experiments, we investigated: (1) the influence of algal photosynthesis on fungal and bacterial production and the activities of four extracellular enzymes throughout a 54‐day period of microbial colonisation and growth; and (2) the influence of litter stoichiometry on these relationships. Ambient and nutrient‐enriched standing‐dead plant litter was collected and then submerged in wetland pools to allow for natural microbial colonisation and growth. Litter samples were periodically retrieved and transported to the laboratory for experiments manipulating photosynthesis using the photosystem II inhibitor DCMU (which effectively prevents algal photosynthetic activity). Algal ( 14 C‐bicarbonate), bacterial ( 3 H‐leucine), and fungal ( 14 C‐acetate) production, and β‐glucosidase, β‐xylosidase, leucine aminopeptidase, and phosphatase activities (MUF‐ or AMC‐labelled fluorogenic substrates) were measured under conditions of active and inhibited algal photosynthesis. Photosynthesis stimulated overall fungal and bacterial production in both experiments, although the strength of stimulation varied amongst sampling dates. Phosphatase activity was stimulated by photosynthesis during the first, but not the second, experiment. No other enzymatic responses to short‐term photosynthesis manipulations were observed. Microbial communities on high‐nutrient litter occasionally showed increased extracellular enzyme activity, fungal growth rates, and bacterial production compared to communities on non‐enriched litter, but algal and fungal production were not affected. Litter stoichiometry had no effects on fungal, bacterial, or enzymatic responses to photosynthesis, but the mean enzyme vector analysis angle (a measure of P‐ versus N‐acquiring enzyme activity) was positively correlated to litter N:P, suggesting that elevated litter N:P led to an increase in the relative activity of P‐acquiring enzymes. These results supported the hypothesis that algal photosynthesis strongly influences heterotrophic microbial activity on macrophyte leaf litter, especially that of fungi, throughout microbial community development. However, the strength of this photosynthetic stimulation does not generally depend on small differences in litter nutrient content. Stimulation of microbial heterotrophs by algal photosynthesis could drive diurnal shifts in periphyton community and aquatic ecosystem function, as well as linking green (photoautotroph‐based) and brown (detrital‐based) food webs.